2011
DOI: 10.1186/1471-2407-11-154
|View full text |Cite
|
Sign up to set email alerts
|

The natural triterpene maslinic acid induces apoptosis in HT29 colon cancer cells by a JNK-p53-dependent mechanism

Abstract: BackgroundMaslinic acid, a pentacyclic triterpene found in the protective wax-like coating of the leaves and fruit of Olea europaea L., is a promising agent for the prevention of colon cancer. We have shown elsewhere that maslinic acid inhibits cell proliferation to a significant extent and activates mitochondrial apoptosis in colon cancer cells. In our latest work we have investigated further this compound's apoptotic molecular mechanism.MethodsWe used HT29 adenocarcinoma cells. Changes genotoxicity were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 42 publications
3
75
1
Order By: Relevance
“…However, it is known that caffeine and maslinic acid induce apoptosis in various vertebrate cell types. For example, caffeine induce PCD in neuroblastoma cells and pancreatic and lung adenocarcinomas (27,28,29,30) and maslinic acid induces apoptosis in metastatic cell lines and in colon cancer cells (31,32). We could find no study in which either drug was reported to induce PCD in any protist.…”
Section: Discussionmentioning
confidence: 98%
“…However, it is known that caffeine and maslinic acid induce apoptosis in various vertebrate cell types. For example, caffeine induce PCD in neuroblastoma cells and pancreatic and lung adenocarcinomas (27,28,29,30) and maslinic acid induces apoptosis in metastatic cell lines and in colon cancer cells (31,32). We could find no study in which either drug was reported to induce PCD in any protist.…”
Section: Discussionmentioning
confidence: 98%
“…Truncated-Bid in turn initiates the mitochondrial pathway. Pro-apoptotic Bid targets the mitochondria and regulates other apoptotic-related protein such as Bcl-2, Bcl-xL and Bax (Reyes-Zurita et al, 2011). The intrinsic pathway plays a key role in regulating cell death through mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the induction of apoptosis has been documented to be one of the major mechanisms underlying the anti-tumor activity of MA. e apoptotic pathway can be triggered by MA, both in mitochondriadependent and -independent ways [8,11]. e association of p38 MAPK signaling with MA's anti-tumor activity has also been indicated in previous studies.…”
Section: Discussionmentioning
confidence: 69%